2016
DOI: 10.1111/trf.13886
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic meningitis following therapy with immune globulins: a combination of product features and patient characteristics?

Abstract: In contrast to previously published data, AM was observed in both low-dose and high-dose regimens without favoring high IG doses, and females were affected nearly four times more often than males. Immunoglobulin G dimers may play a role in the etiology of AM, and subcutaneous administration may be associated with a lower rate of AM compared with intravenous administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…It had been suggested that history of migraines, female sex and underlying connective tissue disease such as systemic lupus erythromatosus could be potential risk factors for developing aseptic meningitis after IVIG. 13,14,15 Further evidences are needed to evaluate whether juvenile dermatomyositis could be a risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It had been suggested that history of migraines, female sex and underlying connective tissue disease such as systemic lupus erythromatosus could be potential risk factors for developing aseptic meningitis after IVIG. 13,14,15 Further evidences are needed to evaluate whether juvenile dermatomyositis could be a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to IVIG-related risk factors, particularly the dosage and the infusion rate, evidence remains disputable. 8, 13 We do not know why some IVIG brands seem to be more likely to cause aseptic meningitis. It was thought that it could possibly be related to the IgA concentration given that the administration of IVIG containing IgA may cause dramatic clinical reactions in patients with serum anti-IgA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A pesar de tratarse de una inmunodeficiencia, los trastornos autoinmunes son frecuentes en el SWA, en-El aumento de la proteinorraquia se ha reportado en casos aislados con el uso de inmunoglobulina, siendo secundario a una meningitis aséptica 20 . Pensamos que la hiperpoteinorraquia en este paciente, se explica principalmente por la inflamación radicular propia del SGB.…”
Section: Discussionunclassified